Theatre pedagogy in the era of climate crisis - Fancy, David; Alexandrowicz, Conrad (Abingdon, Oxon ; New York Routledge,Taylor & Francis Group, 2021)
"This volume explores whether theatre pedagogy can and should be transformed in response to the global climate crisis. Conrad Alexandrowicz and David Fancy present an innovative re-imagining of the ways in which the art of theatre, and the pedagogical apparatus that feeds and supports it, might contribute to global efforts in climate protest and action. Comprised of contributions from a broad range of scholars and practitioners, the volume explores whether an adherence to aesthetic values can be preserved when art is instrumentalized as protest, and considers theatre as a tool to be employed by the School Strike for Climate movement. Considering perspectives from areas including performance, directing, production, design, theory and history, this book will prompt vital discussions which could transform curricular design and implementation in the light of the climate crisis. Theatre Pedagogy in the Era of Climate Crisis will be of great interest to students, scholars and practitioners of climate change and theatre and performance studies"-- Provided by publisher.
Conrad Alexandrowicz, MFA, is an associate professor in the Department of Theatre at the University of Victoria, where he teaches movement for actors. He had a lengthy career as a performer and creator of physical theatre, and has been a dancer, choreographer, playwright, director and producer. His first book, Acting Queer: Gender Dissidence and the Subversion of Realism, was published in February 2020. David Fancy, PhD, is full professor and chair in the Department of Dramatic Arts in the Marilyn I. Walker School of Fine and Performing Arts at Brock University. He publishes on philosophy, technology, environmentalism, disability and performance and has a creative practice as a playwright and director of theatre, opera, and circus. He is editor of a website on the subject of diversities and actor training.
Includes bibliographical references and index.
Keywords: Theater -- Study and teaching; Climatic changes; Theater -- Political aspects; Theater and society